The melliferous flora of Veracruz, Mexico (Agro Productividad, 2021)
Objective: To contribute to the knowledge of the situation of the melliferous flora in Veracruz for pollinators and to communicate it for the benefit of beekeepers and stingless beekeepers, as well as to develop comprehensive strategies with these activities.Design/Methodology/Approach: The information was obtained through a bibliographic review in reference databases such as Scopus, Web of Science Group, Academic Google, Elsevier and Springer Link, using the following keywords: flora, bees, pollinators, honey, pollen.Results: 63 families were recorded, with 176 genera and 216 species of melliferous flora, finding that the largest number of species are found in the Fabaceae family (20%) and Asteraceae (16.55%). There were also 44 crops with 22 families.Study Limitations/Implications: There were no limitations in conducting this study.Findings/Conclusions: The greatest diversity of melliferous flora species is seen in wild plants, and strategies need to be implemented for their protection and multiplication. For these actions, various actors must be involved at different levels of government, educational and private institutions, civil society, farmers, beekeepers, and stingless beekeeping. Conservation actions include the use of melliferous plants in gardens and their protection in crops, sites surrounding crops and on edges. It is necessary to preserve natural landscapes and restore damaged ones, as well as to lead favorable practices in pollinator-dependent crops.